61 ROLE OF SMAD AND WNT SIGNALING PATHWAYS IN THE FIBROTIC DIFFERENTIATION OF C3H 10T (1/2) MULTIPOTENT CELLS INDUCED BY MYOSTATIN. Issue 1 (1st January 2007) - Artaza, J. N.; Singh, R.; Ferrini, M.; Tsao, J.; Braga, M.; Gonzalez-Cadavid, N.
Abstract : Fibrosis (progressive scarring) is a leading cause of organ failure worldwide. Our results indicate that myostatin (Mst), the only known negative regulator of muscle mass, induces the appearance of myofibroblasts in a multipotent cell line (C3H 10T [1/2]) of mouse origin. In this study we show that Mst induces collagen deposition in this cell line, promoting fibrosis, and that this process is mediated through the Smad and Wnt signaling transduction pathways and some of their downstream components. C3H 10 T (1/2) cells were incubated for 2 days with 5′-azacytidine to induce differentiation and then treated with R-Mst (4 μg/mL) in a time course manner (0.5, 1, 2, 3, 24 hours and 3 days); TGF-β (10 ng/ml) was used as a positive control. Cells were also transfected with pcDNA-Mst and two different Mst-shRNA plasmids to overexpress and to silence Mst expression, respectively. Transcriptional regulation of the Smad and Wnt signaling components and induction of genes involved in collagen synthesis were evaluated by three different pathway focus designed microarrays, which have genes each one related to the TGF-β-BMP, osteogenesis, and Wnt signaling pathway. Results were confirmed by immunocytochemistry (ICC) for PAI-1, TGF-β1, collagen I, III and p-Smad 2/3, 3, 4, and 7. The total RNA from cells treated with R-Mst for 3 Hs and 3 days was analyzed by microarrays and qRT-PCR. In parallel, cells were fixed with 2% p-formaldehyde and analyzed by ICC. The main results of the microarray analysis at 3 hours showed that procollagen type IIα1, IVα6, IXα1, 3, Smad 3, TGF-β1, Smad-7, and Fst (follistatin), an inhibitor of Mst activity, and Wntif1 were up-regulated; β-catenin, Wnt 4, ctbp1 were down-regulated, and Smad-1, 2, 5, and 6 did not change. After 3 days of incubation with R-Mst: procollagen type IIα1, IVα6, IXα1, 3, Fst, and Smad 7 were up-regulated and β-catenin, Wnt 4, and ctbp1 were down-regulated, whereas Smad 1, 2, and 5 remained the same and Smad 3 was undetectable. Again, the results for collagen I and III, p-Smad 2/3, 3, 4, and 7 were confirmed by ICC, and, in general, the results from the microarrays were confirmed by quantitative RT-PCR and RT 2 PCR profiler array. In conclusion, Mst induces the expression of PAI-1, TGF-β1, and collagen deposition in C3H 10 T (1/2) cells by signaling through the Smad /Wnt signaling pathway.